Heterogeneity of Regional Growth in the European Union - Martin Wagner; Achim Zeileis (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
This paper uses model-based recursive partitioning to study economic growth in the 255 European Union NUTS2 regions over the period 1995-2005. The starting point of the analysis is a human-capital augmented Solow-type growth equation similar in spirit to Mankiw, Romer, and Weil (1992). Initial GDP and the share of highly educated in the working age population are found to be important for explaining economic growth, whereas the investment share in physical capital is only significant for coastal regions in the PIIGS countries. Recursive partitioning leads to a regression tree with four terminal nodes with partitioning according to (i) capital regions, (ii) non-capital regions in or outside the so-called PIIGS countries and (iii) inside the respective PIIGS regions furthermore between coastal and non-coastal regions.
Keywords: C31; C51; O18; O47; 330; convergence; growth regressions; recursive partitioning; regional data